Automated Driving Vehicle Using Image Processing - Jain, Ashna; Reddy, Harshitha; Dubey, Sarthak (International Journal of Computer Sciences and Engineering, 2014)
This paper focuses on control and automation of intelligent road symbol detection system for vehicles in normal environment conditions. The objective is to look for matching information or some data in the input images that are taken by the overhead mounted camera. The whole setup then filters the noise and other requirements to obtain a steady flow of information for the vehicle to be guided automatically. Here we have used MATLAB for image processing and a microcontroller interfaced with it for actual real time processing and actuation of commands. The functions attributed in the whole setup are direction control mechanism, UART Communication and MATLAB. The results obtained are shown along with neatly explained algorithm and flowchart.